2011
DOI: 10.1055/s-0030-1270487
|View full text |Cite
|
Sign up to set email alerts
|

Validating Two Systems for Estimating Force and Power

Abstract: This study examined the validity of 2 kinematic systems for estimating force and power during squat jumps. 12 weight-trained males each performed single repetition squat jumps with a 20-kg, 40-kg, 60-kg and 80-kg load on a Kistler portable force plate. A commercial linear position transducer (Gymaware [GYM]) and accelerometer (Myotest® [MYO]) were attached to the bar to assess concentric peak force (PF) and peak power (PP). Across all loads tested, the GYM and MYO estimates of PF and PP were moderately to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 19 publications
5
79
0
9
Order By: Relevance
“…6,11 The criteria for statistical significance was set at p=0.05. Correlation values were interpreted according to scale developed by Hopkins: 0.0-0.1, 0.1-0.3, 0.3-0.5, 0.5-0.7, 0.7-0.9, and 0.9-1.0 were interpreted as trivial, small, moderate, large, very large, and nearly perfect.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6,11 The criteria for statistical significance was set at p=0.05. Correlation values were interpreted according to scale developed by Hopkins: 0.0-0.1, 0.1-0.3, 0.3-0.5, 0.5-0.7, 0.7-0.9, and 0.9-1.0 were interpreted as trivial, small, moderate, large, very large, and nearly perfect.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…A standard instrument to measure kinematic qualities of movement is three-dimensional (3D) motion capture hardware and software. As in past studies for validation purpose on kinetics and kinematics, different types of devices are being used, 6 but 3D motion capture system was deemed a satisfactory criterion measure to test that the PUSH™ device as it is capable of reporting accurate data with minimal errors. The device is relatively new and its data acquisition accuracy requires examination scientific examination in order to determine its reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Pour mesurer le temps passé immobile ou bien en mouvement tout au long d'une journée dans le but par exemple de définir le degré de sédentarité on utilisera plutôt un accéléromètre avec une fréquence comprise entre 25 et 60 Hz (Bouten et al, 1997 ;Chen et al, 2005 ;Cleland et al, 2013 ;Kavanagh et al, 2008). Pour la mesure des accélérations d'un point sur le corps lors d'un saut ou d'une course ou bien encore d'une barre de musculation on utilisera des fréquences allant de 100 à 1000 Hz (Choukou et al, 2014 ;Crewther et al, 2011 ;Jidovtseff et al, 2006 ;Sato et al, 2009). Plus le mouvement est dynamique et plus la fréquence d'enregistrement devra être élevée si on veut obtenir une image précise du mouvement analysé sans erreur lors des procédures de calcul.…”
Section: Figure 2 Mesure De L'inclinaison à Partir D'un Accéléromètrunclassified
“…Plusieurs études récentes ont étudié la validité de l'accélérométrie dans des conditions de mouvement non guidées, plus proches de la réalité de terrain (Bampouras et al, 2013 ;Comstock et al, 2011 ;Crewther et al, 2011 ;McMaster et al, 2013 ;Sato et al, 2009). Les résultats ne semblent pas montrer l'existence d'un biais plus important lorsque le mouvement n'est pas guidé.…”
Section: Figure 10 Corrélation Entre Les Valeurs De Pmax Obtenues Paunclassified
“…Another study showed a comparison of the accelerometer and force platform measures during jumping and found moderate levels of agreement between devices when measuring vertical peak force [7]. Similarly, vertical forces were examined in squats and found moderate to high correlations between forces from an accelerometer and force platform [8]. By contrast, very good agreement between devices was found in determining flight times 1 in vertical jumps [9].…”
Section: Introductionmentioning
confidence: 99%